STUDY ON THE UTILIZATION OF LOCAL HISTORICAL HERITAGE OF JAPANESE FORTS IN BADEAN VILLAGE AS AN EFFORT TO INCREASE THE INTEREST IN LEARNING HISTORY OF MTS NURUL IMAN STUDENTS: Studi Pemanfaatan Warisan Sejarah Lokal Benteng Jepang di Desa Badean sebagai Upaya Meningkatkan Minat Belajar Sejarah Siswa MTs Nurul Iman - Hairul Umam; mahfud; Dian Arief Pradana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Interest in learning history among students, especially in rural areas of Indonesia, has decreased significantly, so that only about 35% of students show high interest in the subject. This condition has the potential to threaten their understanding of culture and national identity. This study aims to examine the use of the Japanese Fortress located in Badean Village as a source of history learning to increase the learning interest of MTs Nurul Iman students. A qualitative approach with an exploratory design is applied to explore the experiences and perceptions of students, teachers, and the community through in-depth interviews, participatory observations, and focused group discussions. The results of the study revealed that visits and hands-on learning at the Japanese Fort site were able to increase students' interest and understanding of history. Interactive and contextual learning experiences encourage deeper emotional engagement of students. In addition, the use of these local historical sites helps students identify and live the cultural values inherent in their communities. These findings show the effectiveness of the Japanese Fortress as a historical educational medium in strengthening the cultural identity and learning motivation of MTs Nurul Iman students. The research recommends the need for adequate education policy support, special training for teachers, and improvements to the physical facilities of the site to optimize the use of local historical heritage. The integration of historical sites into the formal curriculum is also suggested as a strategic step in improving the quality of history learning in Indonesia as a whole.